Evaluating Learning in Laboratory Settings - Wendy J. Warner; Brian E. Myers (EDIS)
AEC-379, a 4-page illustrated fact sheet by Wendy J. Warner and Brian E. Myers, describes appropriate strategies for assessing learner achievement in settings where the learner is interacting with materials or models to better observe and understand to the topic at hand. Concept maps, Vee maps, and portfolios are discussed. Includes references. Published by the UF Department of Agricultural Education and Communication, November 2006.